255 A QUALITATIVE STUDY OF OLDER ADULTS' EXPERIENCES OF EMBEDDING PHYSICAL ACTIVITY WITHIN THEIR HOME CARE SERVICES. (18th November 2021) - Galvin, R; Burton, E; Cummins, V; O'Sullivan, M; Swan, L; Doyle, F; Sorensen, J; Skelton, D A; Townley, B; Rooney, D; Jackson, G; Warters, A; et al.
Abstract: Background: Physical activity programmes have been shown to improve older adults' functional capacity, independence and quality of life. Research around structured exercise programmes has been completed in different groups of community-dwelling older people, however few studies have focused on the older population receiving formal home care. In a feasibility study, we embedded physical activity within older adults existing home care services through the 'Care to Move' (CTM) programme. The aim of this qualitative study is to explore older adults' experiences of the CTM programme. Methods: We conducted semi-structured telephone interviews with 13 older adults and one carer. Topics covered included participants overall experiences of the CTM programme, changes to their overall activity and participation, aspects of the programme that they liked or found valuable and issues that they found challenging. Interview transcripts were coded and analysed thematically to capture barriers and facilitators to programme delivery. Results: Four themes emerged: i) 'I'm feeling good about it', ii) 'safety and security is the name of the game', iii) 'we're a team as it stands', iv) 'it's [COVID] depressing for everybody at the moment'. Older adults identified benefits of CTM participation including improvements in physical and psychological wellbeing. However, frailty and multimorbidity influenced overall engagement. Participants expressed concerns around the logistics of programme delivery and competing healthcare assistant (HCA) interests. The broader role of HCA's in supporting the CTM programme was highlighted as well as the emotional support that HCAs provided to older adults. HCA continuity was identified as a barrier to ongoing programme engagement. The impact of COVID on older adults physical and mental health negatively impacted programme delivery. Conclusion: Our findings suggest that embedding the CTM programme within home support services is feasible. Restructuring of services, addressing HCA continuity, and adopting individual approaches to programme delivery may enhance the implementation of services.